Avaliação comparativa pelos testes micropush-out e micro-cisalhamento da resistência adesiva de restaurações diretas de resina composta usando diferentes sistemas adesivos - Pereira, Cristina Alves (2008)
The bond strength may be influenced by the different composition and manipulation of the adhesive systems, the dentin structure and the method of evaluation. After exposure of the occlusal dentin surface 160 third human molars were divided in 2 groups (n=80) for the micropush-out (μPBS) and microshear (μSBS) bond strength tests. For the μPBS, 4 groups (n=20) were obtained and a tapered cavity (2,5x1,5x1,0mm) was prepared on the dentin surface and restored with composite resin after treatment using different adhesive systems: Adper Single Bond, Adper Scotchbond MP, Prompt-L-Pop, AdheSE. After water storage for 24 hours, from 10 teeth per group, 1 oclusal slice (1,5 ±0,3mm) was obtained from each tooth, and the restoration submitted to vertical load. The other 10 teeth were storage for 12 months and then submitted to the same procedure. For the μSBS another 80 teeth were divided into 4 groups (n=20), the dentin surface was treated using the same adhesive systems and composite resin cylinders (1x1mm) were constructed and polymerized in a single increment onto the bonding area. Ten specimens were tested after 24 hours and 10 after 12 months of water storage. The null hypotheses were that (1) the composition and manipulation of the adhesive systems, (2) the water storage and (3) the method of evaluation might influence the bond strength of direct composite resin restorations. Results of ANOVA did not show significant difference for the storage time factor (p=.6343), but there was difference between the methods (p<.0001), with higher values for the μPBS test, and among the adhesive systems (p<.0001). The Adper Scotchbond and AdheSE systems presented higher bond strength values. Adhesive x method (p=.0002) and adhesive x method x time (p=.0037) interactions were significant, with different behaviors from adhesive systems within the method and time of evaluation. Conclusions were that the storage time might be not sufficient to result in alterations and that adhesive systems composition and manipulation might influence the bond strength. The μPBS test, presented the higher bond values with lower coefficient of variation, indicating more consistence than the μSBS test, besides of reproduce more faithfully clinical conditions.